Censo de los empíricos en odontología radicados en montería. Impacto de la ley 100 sobre su ejercicio e identificación de sus características educativas y socioeconómicas - Castro-Núñez, Jaime Alberto (Revista Facultad de Odontología Universidad de Antioquia, 2009)
The empiric dentists living in Montería (Colombia) were censed to know how 100 Law has influenced on their practice and to identify features about kriowledge, socio-economice! and personal situation. The items included into the census were: delimited territory, simultaneous, universelity and direct matching. The previous list was given by Asodenta (an empiric dentists essocietion), the dental otIices were Iocslized and contected by phone, then, there weremade matching and database collection (through and structured inquiry} and the obteined intormetion was analyzed and systematized. There are 32 empiric dentists in Montería, 5missing examination and 5 who were considered to lack the features for being included in the study, so the detinitive sample consisted of 22 subjects. It was found that every 4.7 years an empiric dentist come into the city, being the average age 47 years old and the average time of practice of 26 years. The results showed that they have a low scholership level, most of them got their knowledge from a dentist or an empiric dentist. Besides, it was shown that there was, because of the establishment of 100 Lew. a drop in the number of petients, which generated economical and working instability.